2022
DOI: 10.1021/acs.jafc.2c04126
|View full text |Cite
|
Sign up to set email alerts
|

Odorant-Binding Protein 3-Oriented Rational Design and Discovery of Novel Jasmonate Derivatives as Potential Aphid-Repellent Agents

Abstract: Odorant-binding protein (OBP) is a potential target for developing insect behavior control agents due to its properties in transporting semiochemicals. In this study, 12 novel jasmonic acid (JA) derivatives were rationally designed and synthesized based on the binding features between Acyrthosiphon pisum OBP3 (ApisOBP3) and compound D1 [(E)-3,7-dimethylocta-2,6-dien-1-yl 2-(3-oxo-2-pentylcyclopentyl)­acetate] with a binding affinity (K d) of 26.79 μM. Most novel JA derivatives displayed better binding affiniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…6 Unexpectedly, as shown in Figure 2I, after 6methylcoumarin treatment for 24, 48, and 72 h, there was no difference in the proportion of aphids on the treated or control side of cotton leaves, demonstrating that 6-methylcoumarin exhibited no repellent activity against aphids. It has been reported that most of the natural products with repellent activity against aphids are volatile, such as lemon, 40 jasmonic acid, 41 and farnesol. 39 However, in this study, 6-methylcoumarin does not possess these properties, which may be the reason for its lack of repellent activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…6 Unexpectedly, as shown in Figure 2I, after 6methylcoumarin treatment for 24, 48, and 72 h, there was no difference in the proportion of aphids on the treated or control side of cotton leaves, demonstrating that 6-methylcoumarin exhibited no repellent activity against aphids. It has been reported that most of the natural products with repellent activity against aphids are volatile, such as lemon, 40 jasmonic acid, 41 and farnesol. 39 However, in this study, 6-methylcoumarin does not possess these properties, which may be the reason for its lack of repellent activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1(a,b). [8][9][10][11][12][13][14][15] (E)-⊎-farnesene (EBF) is the main component of aphid alarm pheromones, which are emitted by aphids to warn their conspecifics to leave the area in case of danger. 9 This pheromone also serves as a signal for natural enemies of aphids to locate their prey.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the stability of EBF, researchers have extensively modified the conjugated diene in EBF that is susceptible to oxidation by increasing the molecular weight, reducing unsaturation, and introducing active fragments of other plant volatiles. [10][11][12][13][14][15][20][21][22][23] Furthermore, studies on EBF have been conducted to better understand the mechanisms of action. Odorant binding proteins 3 (OBP3), OBP5, and OBP9 in aphids have been found to have high binding affinity to EBF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations